PENGOBATAN DAN PENILAIAN STATUS GIZI ANAK SDN 1 LUWUS, BATURITI YANG MENDERITA CACINGAN (SOIL- TRANSMITTED HELMINTHIASIS) - DAMAYANTI, P. A. ASRI (Buletin Udayana Mengabdi, 2012)
ABSTRACT During public health services at Sekolah Dasar 1 (primary school) Luwus, a number of 54 out of 140 schoolchildren were treated for helminthiases. Diagnoses of infections were based on their faecal samples examination by Kato-Katz smear technique. The prevalence rate of intestinal helminthic infection was 38,57%. Ascaris lumbricoides was found to be more dominant than Trichuris trichiura. Albendazol 400mg as a single dose for those who suffered Ascaris lumbricoides and Albendazole 400 mg daily for two days for those who suffered Ascaris lumbricoides mix with Trichuris trichiura and Ascaris lumbricoides mix with Enterobius vermicularis. Treatment was done at school in the morning to prevent them from losing such treatment. No side effects were found during treatment.